(untitled) (Lex Journal : Kajian Hukum dan Keadilan, 2025)
The handling of divorce cases in Indonesia is normatively regulated through two different judicial channels, namely the District Court for non-Muslims and the Religious Court for Muslims. This research aims to analyze the comparison between civil procedural law and religious court procedural law in divorce cases, as well as to examine the juridical implications when Muslims file cases with the District Court, which is not the forum with absolute authority. The research uses a normative and comparative juridical approach, by examining Law No. 1 of 1974 concerning Marriage, Law No. 7 of 1989 concerning Religious Courts (which has been amended by Law No. 3 of 2006), and HIR/RBg as the basis for procedural law. The results show that there are fundamental differences in formal-procedural aspects, including in the mediation mechanism, evidence, and the type of divorce certificate issued. In addition, the filing of a divorce lawsuit by a Muslim party to the District Court creates a mismatch in absolute competence and has the potential to cause juridically invalid decisions. Therefore, the understanding of the public and law enforcement officials about the limits of judicial competence is very important to ensure legal certainty and protection of the rights of justice seekers in divorce cases.